Proyeksitas Perlindungan Hukum Terhadap Pekerja Rumah Tangga Dalam Ketentuan Alokasi Waktu Kerja Berdasarkan Hukum Posistif - Fadel Afandi; Mutia CH. Thalib; Mohamad Rivaldy Moha (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This study aims to determine and analyze the protection of domestic workers related to working time and to determine what legal remedies can be done in the event that working time exceeds working time in general. Researchers use the type of normative juridical research. This writing focuses on literature research in the form of collecting legal materials with legal approaches and concepts that are analyzed in a legal perspective. The results of this study indicate that: (1) Regulation No. 2 of 2015 on the protection of domestic servants (PRT) has not been able to reach the Act No. 13 of 2003 in the employment relationship. Since domestic workers are considered not employed “employers", they do not get the protection that the law gives to other workers. (2) the Ideal worker timing Model for domestic workers in Indonesia is still unclear. Domestic workers in Indonesia are still very vulnerable to exploitation related to inhumane working hours, especially for domestic workers who live with their employers. Therefore, it is expected that the government can immediately ratify the Domestic Workers Bill into the Domestic Workers Act